May I Smell Your Attention: Exploration of Smell and Sound for Visuospatial Attention in Virtual Reality - Dozio, Nicolò; Maggioni, Emanuela; Pittera, Dario; Gallace, Alberto; Obrist, Marianna (Frontiers in Psychology, 2021)
When interacting with technology, attention is mainly driven by audiovisual and increasingly haptic stimulation. Olfactory stimuli are widely neglected, although the sense of smell influences many of our daily life choices, affects our behavior, and can catch and direct our attention. In this study, we investigated the effect of smell and sound on visuospatial attention in a virtual environment. We implemented the Bells Test, an established neuropsychological test to assess attentional and visuospatial disorders, in virtual reality (VR). We conducted an experiment with 24 participants comparing the performance of users under three experimental conditions (smell, sound, and smell and sound). The results show that multisensory stimuli play a key role in driving the attention of the participants and highlight asymmetries in directing spatial attention. We discuss the relevance of the results within and beyond human-computer interaction (HCI), particularly with regard to the opportunity of using VR for rehabilitation and assessment procedures for patients with spatial attention deficits.